2004
DOI: 10.1007/s00270-004-0228-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the 10th and 11th Intercostal Space a Safe Approach for Percutaneous Nephrostomy and Nephrolithotomy?

Abstract: The aim of this study was to determine the rate of complications in percutaneous nephrostomy (PCN) and nephrolithotomy (PCNL) performed through the 11th and 10th intercostal spaces using our monitoring technique and to discuss the safety of the procedure. Out of 398 PCNs and PCNLs carried out during a 3-year period, 56 patients had 57 such procedures performed using an intercostal approach. The 11th intercostal route was used in 42 and the 10th in 15 cases. One patient had two separate nephrostomies performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…A similar low complication rate was reported by Muzrakchi and coworkers. 15 Ng et al 9 evaluated the role of noncontrast, prone-position inspiratory and expiratory three-dimensional CT scans for preoperative planning in patients with complex upper-pole renal calculi. On the basis of their small pilot study, they suggested that global recommendations regarding the safety of upper-pole percutaneous access in the inspiratory or expiratory phase do not appear justified, which may TUBELESS SUPRACOSTAL ACCESS FOR PCNL 1019 explain the conflicting literature in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar low complication rate was reported by Muzrakchi and coworkers. 15 Ng et al 9 evaluated the role of noncontrast, prone-position inspiratory and expiratory three-dimensional CT scans for preoperative planning in patients with complex upper-pole renal calculi. On the basis of their small pilot study, they suggested that global recommendations regarding the safety of upper-pole percutaneous access in the inspiratory or expiratory phase do not appear justified, which may TUBELESS SUPRACOSTAL ACCESS FOR PCNL 1019 explain the conflicting literature in this area.…”
Section: Discussionmentioning
confidence: 99%
“…3 The most important disadvantage of the supracostal approach is its associated pleural complications, with a rate ranging from 0 to 37%. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] It is believed that placing a large nephrostomy tube at the end of procedure could limit these complications by allowing free drainage of urine and tamponading the PCNL tract, but such tubes are associated with more postoperative pain and analgesic use. 16 Tubeless PCNL is advocated increasingly in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Each segmental artery then runs upward to reach the corresponding IS, thus giving a more apparent ascending course in the upper thoracic region. Dissection studies have also demonstrated considerable variation in the position of the neurovascular bundle, which may be located at varying distances below the costal groove within the IS (16,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Mousavi-Bahar et al 3 reviewed their complications from supracostal punctures for PCNL in 123 patients, and pneumothorax was found in only 3 cases (2.4%). Similarly, Muzrakchi and coworkers 14 reported complications of PCNL during supracostal 12th rib and supracostal 11th rib access; only 2 patients had minor chest complications in this study.…”
Section: Discussionmentioning
confidence: 78%